Comparing ChatGPT’s and Teacher’s Feedback in Improving EFL Students' Narrative Writing - Priskila Go; Humiras Betty Sihombing (CV. ALIM'SPUBLISHING, 2026)
The rapid advancement of artificial intelligence (AI) has created new opportunities for providing feedback in writing instruction. This study examined the effect of ChatGPT-generated feedback on students’ narrative writing performance and compared its effectiveness with teacher feedback. A quasi-experimental design was conducted with two groups of Grade XI students at SMAN 65 Jakarta. The experimental group received feedback from ChatGPT, while the control group received teacher feedback. Students completed pre-tests and post-tests consisting of narrative writing tasks assessed using Jacobs’ ESL Composition Profile Rubric. Data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test due to non-normal distribution. The results showed that ChatGPT-generated feedback significantly improved students’ writing performance (p < 0.05). However, no significant difference was found between the improvements achieved by the ChatGPT and teacher-feedback groups (p = 0.285). These findings indicate that ChatGPT can be a useful supplementary tool in writing instruction, while teacher feedback remains essential for providing personalized guidance.